Interior Design (1997)
Blauel Archtects, Cyberia Internet Cafe, Centre Pompidou Paris; Arad, Ron, Adidas Dafe, Toulon
Keywords: DISEÑO; DISEÑO DE INTERIORES; LOCALES COMERCIALES; FRANCIA; BARES; CENTROS CULTURALES